If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2a+8)(a+1)=0
We multiply parentheses ..
(+2a^2+2a+8a+8)=0
We get rid of parentheses
2a^2+2a+8a+8=0
We add all the numbers together, and all the variables
2a^2+10a+8=0
a = 2; b = 10; c = +8;
Δ = b2-4ac
Δ = 102-4·2·8
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-6}{2*2}=\frac{-16}{4} =-4 $$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+6}{2*2}=\frac{-4}{4} =-1 $
| 5(-4x+6)=-10 | | 6=7(10d+3)+9 | | 6=7(10d+3 | | 2/5=w+8/4 | | 8=3/2w-4 | | 2x+1-7x=1 | | -16+x=-12 | | x=3-2x+5=10 | | 5x=8-2(2x-6) | | 50=-10000h | | 1x/3-1x/2=12 | | |8e|=24 | | 2x-7+5x=-7 | | 4x+2x-3=7x+8 | | (5u+2)(9+u)=0 | | (X+6)(x-7)=-7 | | -6(3x-2)=-18x-12 | | 8x-7=3x+1 | | 38x+1=-59-21x | | (Y-4)(y+3)(2)+(y+5)(y+3)(4)=(y-4)(y+5)(6) | | 6-6×=-2(x+5) | | 2(3x-3)=-3(2x+6) | | 2/3r=-4/9 | | 3x+5+1=7x+35+8 | | 7n-17=60 | | 6=4(10h+2)+7 | | 4/5x+3/5-1/4x=-1/2x+9/10 | | −3∣x+5∣+1=7∣x+5∣+8 | | -13q=7+-16q-6 | | x*3-x*2=12 | | 7(-3+x)=-42 | | 2÷y+5+4÷y-4=6÷y+3 |